Health monitoring system : powered by wireless wearable sensors - Ong, Wai Teck (2014)
Technology has improved leaps by bounds in this modern era. Body sensors used in the medical domains have always been bulky and cabled, often restricting users to electrical outlets and to monitoring systems, hindering the mobility of the patients. However, with the introduction of Wireless Body Area Network (WBAN), a type of Wireless Sensor Networks (WSNs), allows wearable wireless sensors to be distributed across the body and to transmit data back to a central node for processing. These bring about a great convenience to the patients by increasing their mobility and allow constant health monitoring. With the data from the different sensors distributed across the body and from different users, it would be essential that a system is available to further process the data and consolidate them based on the user and the type of sensor. With this system, applications can be developed from the system, retrieving the relevant sensor and user data. The objective of this project is to develop the above system that provides the encapsulation of the algorithms of processing the data from the sensors and to have a clear specification of the interfaces for external applications or components to access. This allows the ease of development of applications, without the need to worry about processing of data from the sensors and mapping them to the relevant users. With the ease of development, developers are able to focus more on the program logic and the user interface to produce a quality application. On top of the system mentioned above, a web application is also developed to allow medical personnel to have an overview of their patients via an intuitive user interface that can be used on different types of devices of different screen sizes such as desktops, mobile phones and tablets. With the use of various web technologies, live health monitoring system and email notification service is also made possible, allowing medical personnel to be always updated of their patients’ constant health monitoring.